An HIV-negative penil Kaposi's sarcoma - (:unkn) unknown (My University, 2004)
Kaposi's sarcoma is a tumour of reticuloendothelial system. Non-epidemic Kaposi's sarcoma limited to the penile involvement should be aggressively treated because it is rarely associated with diffuse organ involvement localized surgical excision or small-field external beam or electron beam radiation has been effective. In this case, we presented a man 53 years old, who presents with a papular indolent lesion on the glans penis, which is reported as a Kaposi sarcoma after excision of the lesion. © 2004 Kluwer Academic Publishers.
Keywords: Glans penis; HIV-negative; Kaposi's sarcoma